PENGARUH SENAM HAMIL TERHADAP PENURUNAN NYERI PUNGGUNG PADA IBU HAMIL DI DESA PA’RAPPUNGANTA KECAMATAN POLONGBANGKENG UTARA KABUPATEN TAKALAR - wirda, Wirda; ernawati, Ernawati (Journal of Islamic Nursing, 2020)
Background: among all pregnant women, it turns out 47-60% reported that back pain occurs in pregnancy 5-7 months and pregnancy exercises can reduce back pain in pregnant women. The aim is to find out the effects of pregnancy exercise on the reduction of back pain in Pregnant Women in Pa'rappunganta Village, Polongbangkeng Utara District, Takalar Regency. The design of this study was Quasy Experiment using a group pre-post test design approach, with a total sampling technique and the sample is 10 pregnant women with a gestational age more than 5 months , This research uses observation sheet. The results of this study were processed using a Wilcoxon alternative testand the value of p = 0.004 <α 0.05. Conclusion shows that there is an effect of pregnancy exercise on decreasing back pain in pregnant women in Pa'rappunganta Village, Polongbangkeng Utara District, Takalar Regency 2019.keywords: Pregnancy Exercise, Back Pain in Pregnant Women